Role of State Institutions in Protecting the Environment. Improving Management System of the Public Services - KIM, Yuliya; DARIBEKOV, Serik; KUNDAKOVA, Laura; SIKHIMBAYEVA, Dinar; SRAILOVA, Gulnara (Journal of Environmental Management and Tourism; Vol 14 No 5 (2023): JEMT, Volume XIV, Issue 5(69), Fall 2023DO - 10.14505/jemt.v14.5(69).19, 2023)
The development and implementation of environmental policy and the application of relevant legislation is an area of public administration responsibility that is important for the protection of the environment . With the growing challenges facing governments around the world, the effective functioning of public services is becoming increasingly important. In the 21 st century, public services based on a capacity-based approach will be a key competitive advantage for states. The provision of key public services, such as health care, sanitation, electricity and water, is critical to achieving global development goals. The relationship between public administration and ecology includes the role of state institutions in environmental protection and sustainable development, as well as the impact of environmental issues on the effectiveness of public administration. Governments around the world should attach great importance to environmental issues, as environmental problems can seriously affect the well-being of the population and the economy.